Changes in cardiovascular health score and atherosclerosis progression in middle-aged and older persons in China: a cohort study. Issue 8 (26th August 2015) - Gao, Jingsheng; Bao, Minghui; Liu, Yan; Shi, Jihong; Huang, Zhe; Xing, Aijun; Wang, Yang; An, Shasha; Cai, Jun; Wu, Shouling; Yang, Xinchun
Abstract : Objectives: The American Heart Association (AHA) proposed a definition of 4 cardiovascular health behaviours and 3 health factors. On the basis of the 7 metrics, the cardiovascular health score (CHS) was used to estimate individual-level changes in cardiovascular health status. The aim of this study was to investigate whether changes in CHS (⊿CHS) at different time-points are associated with atherosclerosis progression in middle-aged and older persons. Design: Prospective cohort study in China. Settings: We defined 8 groups (≤−4, −3, −2, −1, 0, 1, 2 and ≥3) according to ⊿CHS. The impact of ⊿CHS on the change of brachial–ankle pulse wave velocity (⊿baPWV) and atherosclerosis progression was analysed. Participants: A total of 3951 individuals met the inclusion criteria (≥40 years old; no history of stroke, transient ischaemic attack or myocardial infarction) and had complete information. Results: ⊿baPWV decreased gradually (126.46±355.91, 78.4±343.81, 69.6±316.27, 49.59±287.57, 57.07±261.17, 40.45±264.27, 37.45±283.26 and 21.66±264.17 cm/s, respectively) with increasing ⊿CHS (p for trend<0.05). Multivariate linear regression analysis suggested a negative relationship between these 2 variables, which persisted after adjustment for other risk factors. Each increase in CHS was associated with a reduced baPWV for 15.22 cm/s (B value −15.22, p<0.001). Conclusions: ⊿CHS were negatively related to ⊿baPWV, which proved to be an independent predictor of the progression of atherosclerosis in middle-aged and older persons. Trial registration number: Kailuan study (ChiCTR-TNC-11001489).